Management of the complications of pubovaginal sling surgery - ONUR, AHMET RAHMİ (My University, 2017)
To present complications of pubovaginal sling surgery (PVS) and their managements. Methods. A total of 21 patients who underwent PVS in 4 different tertiary refferal centers between June 2014 and May 2016 were reviewed retrospectively. Demographic characteristics of the patients, previous surgical history, daily pad use, Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ) were recorded. Also, the management of the complications were stated. Results. The mean age of the patients were 54.9±12.32 (range, 36-76) years. Six (28.5%) patients had a history of previous incontinence surgery and 15 (71.4%) patients were naïve. There were no intraoperative complications.The mean daily pad use was decreased from 4.04±0.95 to 0.95±0.86 (p=0.0001). While mean preoperative UDI-6 scores were decreased from 6.66±2.09 to 2.09±1.22 (p=0.0001) at postoperative sixth month; preoperative mean IIQ-7 scores decreased from 16.8±1.16 to 5.09±4.21 (p=0.0001) at postoperative sixth month. One (4.76%) patient had abdominal hernia at postoperative 2nd year, three (14.28%) patients had an increased post-micturational residual (150- 200ml) and two (9.52%) patients had urinary retention. Conclusion. Although the efficiency of PVS is high; one should aware of complications. The successful management of the complications will increase efficiency and patient satisfaction.
Keywords: Biyoloji; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji